Association between pre-treatment perfusion profile and cerebral edema after reperfusion therapies in ischemic stroke. Issue 11 (November 2021) - Ng, Felix C; Churilov, Leonid; Yassi, Nawaf; Kleinig, Timothy J; Thijs, Vincent; Wu, Teddy Y; Shah, Darshan; Dewey, Helen M; Sharma, Gagan; Desmond, Patricia M; Yan, Bernard; Parsons, Mark W; et al.
The relationship between reperfusion and edema is unclear, with experimental and clinical data yielding conflicting results. We investigated whether the extent of salvageable and irreversibly-injured tissue at baseline influenced the effect of therapeutic reperfusion on cerebral edema. In a pooled analysis of 415 patients with anterior circulation large vessel occlusion from the Tenecteplase-versus-Alteplase-before-Endovascular-Therapy-for-Ischemic-Stroke (EXTEND-IA TNK) part 1 and 2 trials, associations between core and mismatch volume on pre-treatment CT-Perfusion with cerebral edema at 24-hours, and their interactions with reperfusion were tested. Core volume was associated with increased edema (p < 0.001) with no significant interaction with reperfusion (p = 0.82). In comparison, a significant interaction between reperfusion and mismatch volume (p = 0.03) was observed: Mismatch volume was associated with increased edema in the absence of reperfusion (p = 0.009) but not with reperfusion (p = 0.27). When mismatch volume was dichotomized at the median (102 ml), reperfusion was associated with reduced edema in patients with large mismatch volume (p < 0.001) but not with smaller mismatch volume (p = 0.35). The effect of reperfusion on edema may be variable and dependent on the physiological state of the cerebral tissue. In patients with small to moderate ischemic core volume, the benefit of reperfusion in reducing edema is related to penumbral salvage.